Bichectomy: a narrative review of the literature (Research, Society and Development, 2023)
Bichectomy is an intraoral surgical procedure that involves partial or total removal of the Bichat fat pad, also known as Bichat ball, which is a layer of fat located on the cheeks, between the buccinator muscle and the superficial muscles of the face. This surgery aims to improve facial aesthetics and, in some cases, provide functional benefits. When performed by a trained professional, bichectomy is considered a relatively simple procedure. However, more serious complications can occur, such as edema, hematoma, facial infections, parotid gland duct injury and even facial paralysis. The results of the bichectomy can be observed after about six months, when the subcutaneous tissue swelling is completely absorbed. This procedure is sought both for aesthetic reasons, aimed at slimming the face and improving facial harmony, and for functional reasons, when excess fat in the cheek area causes traumatic injuries due to frequent biting. This work aims to review the existing literature on important aspects of the bichectomy surgery technique.